Results of a Prospective Dose Escalation Study of Linear Accelerator–Based Virtual Brachytherapy (BOOSTER) for Prostate Cancer; Virtual HDR Brachytherapy for Prostate Cancer - Eade, Thomas (Adv Radiat Oncol, 2019)
PURPOSE: To demonstrate feasibility and toxicity of linear accelerator–based stereotactic radiation therapy boost (SBRT) for prostate cancer, mimicking a high-dose-rate brachytherapy boost. METHODS AND MATERIALS: A phase 1 sequential dose escalation study of SBRT compared 20 Gy, 22 Gy, and 24 Gy to the prostate and 25 Gy, 27.5 Gy, and 30 Gy to the gross tumor volume in 2 fractions, combined with 46 Gy in 23 fractions of external beam radiation. Feasibility of dose escalation (volume receiving 125% and 150% of the dose) while meeting organ-at-risk dose constraints, grade 2 acute and late gastrointestinal and genitourinary toxicity, and freedom from biochemical failure were secondary endpoints. RESULTS: Thirty-six men with intermediate- and high-risk prostate cancer were enrolled with a median follow-up of 24 months. Sixty-four percent of patients had high-risk features. Nine men were enrolled to dose level 1, 6 to level 2, and 6 to level 3. Another 15 patients were treated at dose level 3 on the continuation study. Dose level 3 achieved superior 125% (23.75 Gy) and 150% (28.5 Gy) dose compared to dose levels 1 and 2, with minimal differences in organ-at-risk doses. Kaplan-Meier estimate of freedom from biochemical failure at 3 years was 93.3%. There were no late grade 2 or 3 gastrointestinal events. The late grade 2 genitourinary toxicity at 2 years was 19.3%. Prostate-specific membrane antigen positron emission tomography was performed at 2 years with no local recurrences. CONCLUSIONS: We have shown that a linear accelerator–based SBRT boost for prostate cancer is feasible and can achieve doses comparable to high-dose-rate boost up to the 150% isodose volumes. Rectal, bladder, and urethral doses remained low, and long-term toxicity was the same as or better than previous reports from high-dose-rate or low-dose-rate boost protocols.